HUBUNGAN PENGETAHUAN, SIKAP DAN STATUS GIZI TERHADAP KEJADIAN DIABETES MELITUS DI RSUD DR. H. MOHAMAD RABAIN MUARA ENIM TAHUN 2023 - Eliza Meirianti; Eko Heryanto (Jurnal Ilmiah Medsains, 2023)
Diabetes Melitus is a degenerative disease that needs serious attention as a non-communicable disease. Data on visits to Diabetes Melitus patients at RSUD dr. H. Mohamad Rabain Muara Enim in 2022 increased to 1455 people diagnosed with Diabetes Melitus reaching 63.2% with an age of 45 to 65 years. This type of research uses quantitative correlation with a Cross Sectional approach. The population in this study were 1455 patients with Diabetes Melitus who were at Dr. H. Mohamad Rabain Muara Enim Hospital. The sample taken in this study used purposive sampling method. From the results of the analysis it was found that out of 304 respondents, 189 (62.2%) respondents were sick with Diabetes Melitus, 146 (48.0%) respondents had poor knowledge, 159 (52.3%) respondents had negative attitudes, 159 (52.3%) respondents had risky nutritional status. The results of the chi square test showed a significant relationship between knowledge and the incidence of Diabetes Melitus with a p value of 0.000, there was a relationship between attitude and the incidence of Diabetes Melitus with a p value of 0.000 and there was a relationship between nutritional status and the incidence of Diabetes Melitus with a p value of 0.000.